Economic Growth and Public Indebtedness in the Last Four Decades: Is Portugal different from the other PIIGS’ economies? - Ricardo Ferraz; António Portugal Duarte (Naše gospodarstvo/Our economy, 2015)
Portugal is a member of the group known by investors as ‘PIIGS’, countries characterised by having high public debt and weak economic growth. Using an extended time horizon, 1974–2014, this study seeks to empirically explore the relationship between economic growth and public debt in the PIIGS economies, particularly in the case of Portugal. Based on the estimation of linear regression models, it was concluded that in the last four decades there has been a negative relationship between economic growth and public debt in both cases, which is consistent with the literature. The negative relationship was even more pronounced in the case of the PIIGS than it was in the case of Portugal.